2016
DOI: 10.1016/j.bjm.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies of new strains of Trametes sp. from Argentina for laccase production ability

Abstract: Oxidative enzymes secreted by white rot fungi can be applied in several technological processes within the paper industry, biofuel production and bioremediation. The discovery of native strains from the biodiverse Misiones (Argentina) forest can provide useful enzymes for biotechnological purposes. In this work, we evaluated the laccase and manganese peroxidase secretion abilities of four newly discovered strains of Trametes sp. that are native to Misiones. In addition, the copper response and optimal pH and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
11
0
2
Order By: Relevance
“…The capacity of non-pathogenic strains of F. oxysporum to control several fungal diseases has been also demonstrated 35 . Species of the genus Trametes are well known for their ability to produce enzymes, which could assist in the defense of the plant against pathogens 36 . Similarly, species from Pezizomycetes have been reported to offer benefits to their host plants 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of non-pathogenic strains of F. oxysporum to control several fungal diseases has been also demonstrated 35 . Species of the genus Trametes are well known for their ability to produce enzymes, which could assist in the defense of the plant against pathogens 36 . Similarly, species from Pezizomycetes have been reported to offer benefits to their host plants 37 .…”
Section: Discussionmentioning
confidence: 99%
“…5.249, Fructificatio Amaurodermatis Rudae, Ganoderma lucidum, Pleurotus nebrodensis, Phellinus igniarius CGMCC No.8108 , Cordyceps militaris, Boletus edulis, Trametes versicolor CGMCC No.12241 , Trametes robiniophia, Schizophyllum commune, Sclerotium Xylariae Nigripis ) were deposited at the Shandong Province Key Lab of Applied Mycology, China. The fungus was identified based on analysis of internal transcribed spacer sequences 39 40 . The culture medium consisted of glucose (2 g), KH 2 PO 4 (0.2 g), MgSO 4 (0.1 g), and peptone (0.4 g), and agar (4 g, only in solid medium) in 200 mL of sterilized water.…”
Section: Methodsmentioning
confidence: 99%
“…Fonseca and others evaluated the secretion ability of laccase produced by four newly discovered strains Trametes sp. and found that the laccase secreted by one of the strains was highly thermostable and showed its potential in the development of biotechnology [16]. Chen Qionghua [17] and others used Ganoderma weberianum TZC-1 as a production strain and tried to enlarge the strain in a 50L fermentor under the conditions of optimized shake flask culture and a small test production process on a 5L fermentor.…”
Section: The Industrial Process Of Laccasesmentioning
confidence: 99%